Novi upravni postupci u Bosni i Hercegovini / New Administrative Procedure in Bosnia and Herzegovina - Ajanović, Enver (Pregled: časopis za društvena pitanja / Periodical for social issues, 2024)
Laws on administrative procedure in Bosnia and Herzegovina still contain unharmonized normative solutions and close the gap. Because of such weakness substantive private and administrative law application can not to fail under the principle of good governance. Therefore, they need to be further edited by taking over of better solutions from comparative administrative law and by removing of contradictories to create new legal norms. So it will be in all parts administrative procedure created assumptions for establishing of effective authority. Normative text will be longer and will enable more qualitative substantive and international administrative law application transformed in ordinary law. The largest changes are between the principles, because it is necessary to regulate new general legal principles of administrative procedures.